Ejercicio físico en trastornos de ansiedad: una revisión (2022)
Anxiety is one of the major mental health problems in today's society and physical exercise has been proposed as a possible treatment. The aim of the study was twofold: 1) to determine which measurement and monitoring instruments were used for the evaluation of anxiety when a physical exercise program was implemented; 2) to analyze the effectiveness of physical exercise applied for the reduction of anxiety disorder through recent scientific publications. A review was performed using PRISMA method, in PubMed, ScienceDirect, PsycArticles and SPORTDiscus with the descriptors of Anxiety AND Exercise between 2015- 2021. An initial 289 papers were obtained. Criteria were applied finally selecting 22 studies to analyze. The STAI continues to be the most widely used instrument. Physical exercise has been shown to be a valid guideline in reducing anxiety and improving mental health.